A Hybrid Cryptographic Algorithm-based User Authentication and Secured Data Transmission in Blockchain-based Internet of Vehicles (BIOV) Environment - V, Girija.; George G, Victo Sudha (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The emergence of Blockchain-based Internet of Vehicles (BIoV) is driven by disruptive technologies, vital for robust vehicular information systems. Disputes over data rights or security violations can disrupt transportation. Addressing BIoV’s security, a new hybrid cryptographic authentication model is introduced, comprising four steps: data classification, encryption, blockchain-based transfer, and user authentication. Sensitive vehicle data is split and encrypted using Two-Level Advanced Elliptic Curve Cryptosystems (2LAECC). The private key is generated optimally via Enriched Bat Optimizer. Validated recipients receive information based on computed dual-trust scores. The model’s security, encryption, and decryption are validated. This model fortifies BIoV’s future through enhanced security, efficient encryption, and trusted data sharing.